Nadando a casa - Levy, Deborah; Higuera Glynne-Jones, Susana de la; Levy, Deborah (Madrid : Siruela, 2015)
A mysterious woman who suffers from mental illness suddenly appears at a vacation villa where two families are staying and her interactions with them reveal secret details about their past and tensions within their relationships with each other.
Online resource; title from ePub title page (Digitalia, viewed April 14, 2017)
Keywords: Riviera (France) -- Fiction; Romance fiction; Psychological fiction; Electronic books